Efficacy of bio-assisted pelvic floor muscle training in women with pelvic floor dysfunction. (August 2020) - Liu, Ying-Ju; Ting, Stella Wan-Hua; Hsiao, Sheng-Mou; Huang, Chiu-Mieh; Wu, Wen-Yih
Highlights: Training notably improved PFM function in women with PFD. PFMT using surface EMG biofeedback improves PFM function in complex PFD. PFMT has a significant therapeutic effect on OAB, SUI, and bladder prolapse. Abstract: Objectives: To evaluate the efficacy of 12-week pelvic floor muscle training (PFMT) using bio-assisted surface electromyography (EMG) feedback in women with complex pelvic floor dysfunction (PFD); to further differentiate the effect of exercise adherence from the biofeedback per se; and to assess and compare the severities of overactive bladder (OAB) symptoms, stress urinary incontinence (SUI), and stage of prolapse with the women's perception of symptom cure or improvement following the program. Study design: This prospective observational study was conducted between December 2015 and November 2018 at a medical center in Taiwan. It included 83 women with PFD, manifesting solely as either OAB or SUI with (group 1) or without (group 2) concomitant stages I and II pelvic organ prolapse (POP). All women underwent a 12-week bio-assisted PFMT. The main outcome was the electromyographic activity of the pelvic floor muscles (PFMs). The severities of OAB symptoms, SUI, and stage of POP were assessed both subjectively and objectively before and after the intervention. Results: A notable improvement of PFM function was identified after 12 weeks of training in all women with PFD. The number of effective PFM contractions achieved during bio-assisted PFMT was positively correlated with the improvement of PFM function in both groups of women in different body positions, except in the standing position in group 2. Exercise adherence, however, had no significant impact on the efficacy of the training. There was a significant improvement over time and high consistency between subjective and objective improvements of OAB symptoms and SUI severity after the completion of PFMT. Nonetheless, only the Ba point of the POP-Quantification system in women with POP showed a significant improvement after the intervention. Conclusion: PFMT using surface EMG biofeedback significantly improves PFM function in women with complex PFD, and thus, has a significant therapeutic effect on OAB, SUI, and bladder prolapse.